1998
DOI: 10.1136/vr.142.9.207
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prospects for horses with grass sickness (dysautonomia)

Abstract: Responses to questionnaires were received from 31 owners of horses or ponies treated for chronic grass sickness (dysautonomia). Contrary to previous opinions the respondents indicated that the majority of the animals were capable of strenuous work, had regained the weight they had lost and, apart from a few residual problems such as difficulty in coping with dry fibrous food, had returned to a normal life. They had recovered slowly and had involved the owners in considerable extra work, but all the owners indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 6 publications
4
20
0
Order By: Relevance
“…In the present study chronic grass sickness was presumptively diagnosed after considering the nature and progression of clinical signs, history, case background, epidemiological factors and elimination of alternative diagnoses [7]. Diagnosing chronic grass sickness by clinical examination, by clinicians familiar with the disease, has a reported accuracy of 100% [3]. Consistent with these data, all 79 nonsurvivors that had a post mortem examination including histopathological examination of neural tissue were confirmed to have chronic grass sickness.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In the present study chronic grass sickness was presumptively diagnosed after considering the nature and progression of clinical signs, history, case background, epidemiological factors and elimination of alternative diagnoses [7]. Diagnosing chronic grass sickness by clinical examination, by clinicians familiar with the disease, has a reported accuracy of 100% [3]. Consistent with these data, all 79 nonsurvivors that had a post mortem examination including histopathological examination of neural tissue were confirmed to have chronic grass sickness.…”
Section: Discussionsupporting
confidence: 65%
“…This is the largest study to report the outcome of chronic grass sickness cases [1][2][3][4]. The survival rates of 49.4% for all (241) horses hospitalised for management of chronic grass sickness during the study period, and of 53.5% for the 213 horses included in the study, were higher than previously reported (35.6% [1] and 42.7% [2]).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The disease can occur in 3 forms, defined on the basis of clinical signs and severity of the disease (Doxey et al 1991a). T h e acute and subacute forms of the disease are invariably fatal, whereas some milder chronic cases can recover with appropriate treatment, the mainstay of which is currently thorough nursing care (Milne et al 1994;Doxey et al 1995aDoxey et al , 1998Milne 1997). The duration is 12-48 h, in the acute form, and 7 days to several weeks, in the chronic form.…”
Section: Introductionmentioning
confidence: 99%